Experimental games on networks: Underpinnings of behavior and equilibrium selection - Gary Charness; Francesco Feri; Miguel A. Meléndez-Jiménez; Matthias Sutter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
In this paper, we describe a series of laboratory experiments that implement specific examples of a more general network structure and we examine equilibrium selection. Specifically, actions are either strategic substitutes or strategic complements, and participants have either complete or incomplete information about the structure of a random network. Since economic environments typically have a considerable degree of complementarity or substitutability, this framework applies to a wide variety of settings. The degree of equilibrium play is striking, in particular with incomplete information. Behavior closely resembles the theoretical equilibrium whenever this is unique; when there are multiple equilibria, general features of networks, such as connectivity, clustering, and the degree of the players, help to predict informed behavior in the lab. People appear to be strongly attracted to maximizing aggregate payoffs (social efficiency), but there are forces that moderate this attraction: 1) people seem content with (in the aggregate) capturing only the lions share of the efficient profits in exchange for reduced exposure to loss, and 2) uncertainty about the network structure makes it considerably more difficult to coordinate on a demanding, but efficient, equilibrium that is typically implemented with complete information.
Keywords: C71; C91; D03; D85; 330; Random networks; Incomplete information; Connectivity; Clustering; Strategic substitutes; Strategic complements; Experiment